Analysis of the game characteristics of the final juniors (female) match U14 at World Junior Tennis Finals in 2017 (case study) - Janák, O.; Zhánel, J. (Studia Sportiva, 2019)
Analysis of the course of a match serves in many sports as a tool to obtain feedback for players and coaches. The most common method of analysis in tennis is analysis of game characteristics which is used in the training process both in pre-match preparation and post-match analysis. The results of these analysis, centre on different ages and performance cohorts, are published in a number of studies. At present, special computer software is often used to analyze game characteristics in tennis, eg. IBM Slam Tracker is used on all four grandslam tournaments. Game characteristics processed with this software have been taken into account when choosing 13 game characteristics used in our research. The aim of the research was to analyze the game characteristics of the best female junior players(n = 4), participants of the World Junior Tennis Finals (WJTF) final in 2017 in Prostejov. Based on the analysis of the research data, the differences in the level of the game characteristics of the winning and defeated finalists were determined, then comparison of the game characteristics of finalists WJTF 2017 and finalists of the women tournament at Roland Garros (RG) 2017 was carried out. In the final matches between Ukraine (UA) and the United States (US), the selected game characteristics were evaluated using the Dartfish 9.0 software. The results of the analysis of the game characteristics showed that the winning players gained more points after first and second serve in both matches. The winning players also obtained more breaks and winners, committing a significantly lower number of double faults and unforced errors. When comparing the level of game characteristics of the winning players at WJTF, it was found that they had a higher success rate of first serve than the RG winner and had a higher success rate in the number of gained breaks. It was found that the RG winner had a significantly higher ratio of winners over a defeated player than it was by winners at WJTF. The ratio of total points won by the winning players versus the losers was higher for the WJTF than for the RG winner, which suggests a more balanced match at the RG final.